(untitled) (Research, Society and Development, 2022)
The study deals with the right to the city, focused on urban mobility, with the objective of pointing out how public policies related to collective public transport have been applied, based on the master plans of the capitals of the five states of the Brazilian Eastern Amazon. Bibliographic and documentary research was used; as well as exploratory and basic research. Data collection took place using municipal and federal legislation, along with legal doctrine, periodicals, and annals in interdisciplinary areas on the subject. Data analysis took place quantitatively using tables, graphs, and location maps, and qualitatively through descriptive data collection. It was found that the legal provisions in the master plans are not compatible when compared to the studies pointed out in the research, making these municipal legislations pending effectiveness due to their lack of applicability in terms of urban mobility. In this way, the research provides academic and scientific visibility to the issue of urban mobility of the Brazilian Eastern Amazon, and the consequent promotion of dialogue on the subject.